What Can Be Other? The Role of Experience in Philosophy - Elena V. Kosilova (RUDN Journal of Philosophy)
In our time, the so-called experimental philosophy is emerging. Examples of it are the experimental study of cognition, empirical studies of the work of scientists and the development of scientific knowledge (STS), and some other fields. At the same time, philosophical statements claim to be universally valid. Logical positivists held that metaphysical statements are unverifiable and therefore meaningless. According to Kant, knowledge begins with experience, but its results is not derived from experience. Experiential conclusions could be different under other conditions; universally valid conclusions remain true under all conditions. This study attempts to answer the question of how experience enters into philosophical reasoning. First of all, the question arises: how is experience to be understood? Experience can be understood narrowly and broadly. In the latter case, it also includes the experience of thinking (since thinking could be different). However, one cannot deny the possibility of cognizing extra-experiential, including normative, truths. How we distinguish them from truths of fact is still an open question. The experience of our own thinking is given in reflection, while the experience of thinking of different people is studied by cognitive science. The role of experience in philosophical thinking is examined through examples: philosophy of music, neurophenomenology, material of psychopathology, and existential philosophy. In all these areas of philosophy, metaphysical claims are made in one way or another on the basis of experiential data. In conclusion, I formulate my own hypothesis of the role of experience in philosophy: metaphysical judgments follow only from other metaphysical judgments, experience playing the role of a filter. This hypothesis is open for discussion.